آثر أنشطة قائمة على التمثيل الحركي للحروف الأبجدية - شوشاني محمد, صالح; لعيس, إسماعيل (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة لمعرفة أثر أنشطة تعتمد على التمثيل الحركي لحروف الأبجدية العربية في تحسين القراءة (فك الرموز) التهجئة (والإملاء) لذوي العسر القرائي والكتابي, تم تطبيق هذه الأنشطة على (10) تلاميذ من تلاميذ السنة الرابعة ابتدائي بإحدى ابتدائيات مدينة الوادي, استخدمنا فيها المنهج التجريبي بتصميم المجموعة الواحدة باختبار قبلي لاختبار القراءة والإملاء(التهجئة) ثم تطبيق الأنشطة على المشاركين ثم قياس بعدي, فكانت النتائج أن هناك أثر إيجابي في تحسين القراءة والتهجئة لمسناها من خلال الفروق بين متوسطي القياسين القبلي والبعدي الدالة احصائيا عند مستوى (0.05) لصالح القياس البعدي, ومن خلال هذه النتائج خرجت الدراسة بمجموعة من الاقتراحات من أهمها ضرورة تنويع المداخل العلاجية لذوي اضطراب التعلم. Abstract: This study aimed to find out the effect of activities based on the kinematic representation of the letters of the Arabic alphabet in improving reading (decoding) spelling (and spelling) for people with reading and writing dysfunctions. These activities were applied to (10) students from the fourth year of primary school in one of the elementary schools of the Valley City. The experimental approach is by designing one group with a pre-test to test reading and spelling (spelling), then applying activities to the participants and then measuring it afterwards, so the results were that there is a positive effect on improving reading and spelling we touched through the differences between the mean of the pre and post measurements that are statistically significant at the level of (0.05) in favor of the measurement Dimensional, and through these results the study came out with a set of suggestions, the most important of which is the necessity to diversify treatment approaches for people with learning disorder.
مقال
Keywords: التمثيل الحركي؛ فك الرموز؛ التهجئة؛ اضطراب تعلم القراءة والكتابة; Motor representation; Decoding; Spelling; trouble Learn to read and write